Artificial Intelligence that Exists in the Human Mind - Muhammad Rehan Anwar; Fitra Putri Oganda; Nuke Puji Lestari Santoso; Muhamad Fabio (Pandawan Sejahtera Indonesia, 2022)
This article asserts that some general AIs are incomprehensible to humans and that computers are innately incapable of performing certain human cognitive activities, including 1) Misconceptions of Godel's theorem and related statistics and mathematical results are at the root of objections to using AI; 2) Reductionism and objections to monistic reductionism, as well as a minimal appreciation of responses to different levels of discussion; 3) Concerns raised by a thorough understanding of computers or computing Developing a model in which